Strategies to Improve the Learning Outcomes of Elementary School Students in Sports Practice in Padang City - Nabilla Wahyuni Deevona; Wilda Welis; Rika Sepriani; Nugroho Susanto (STKIP Singkawang, 2025)
This study analyzes how nutritional status, physical fitness, and motor skills affect PJOK practical learning outcomes among 54 students at SDN 04 Kampung Olo, Padang. Using path analysis, BMI, fitness tests, and motor skill assessments were used to measure the variables, while learning outcomes were evaluated through PJOK performance. Nutritional status, physical fitness, and motor skills have a significant direct effect on the practical learning outcomes of physical education students in Padang City, with contributions of 37.8% (p = 0.006), 28.8% (p = 0.012), and 25.2% (p = 0.004), respectively. Nutritional status also has an indirect effect through physical fitness, contributing 7.3% (p for the path from nutritional status to physical fitness = 0.065; p for physical fitness to learning outcomes = 0.012) and through motor skills by 4.1% (p path from nutritional status to motor skills = 0.244; p from motor skills to learning outcomes = 0.004), although the influence through motor skills was less significant. Physical fitness had a significant indirect influence through motor skills by 21.1% (p = 0.000 and p = 0.004).